Ukraine in the system of modern international legal order and Еuropean integration : problems of doctrine and practice in the context of modern humanitarian challenges - CHEPEL, Olha; DRĂGHICI, Vasile; FEDOROVA, Alla; HORODYSKYI, Ivan; HNATIUK, Tetyana; ILIKA, Maryna; KARVATSKA, Svitlana; KYRYLIUK, Nataliia; KUZMA, Viktoriya; MALISKA, Marcos Augusto; MELENKO, Sergiy; MITSIK, Vsevolod; et al. (Yuriy Fedkovych Chernivtsi National University, 2022)
The monograph considers the theoretical and practical aspects of the development of modern international law and the place of Ukraine in the and European integration. The monograph sheds light on the problems of doctrine and practice of modern international law in the context of modern humanitarian challenges. The publication is of considerable interest and will be helpful in general for lawyers, international lawyers, undergraduate and postgraduate students, judges, legal practitioners, and all those interested in the problems of international law in its broadest sense.
Cоllective monograph
Keywords: International Law; European Law; International order; International integration; Human Rights; Humanitarian challenges